2019
DOI: 10.1093/pcp/pcz169
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Transcriptomics Analysis of Brassica napus L. during Seed Maturation Reveals Dynamic Changes in Gene Expression between Embryos and Seed Coats and Distinct Expression Profiles of Acyl-CoA-Binding Proteins for Lipid Accumulation

Abstract: Production of vegetable oils is a vital agricultural resource and oilseed rape (Brassica napus) is the third most important oil crop globally. Although the regulation of lipid biosynthesis in oilseeds is still not fully defined, the acyl-CoA-binding proteins (ACBPs) have been reported to be involved in such metabolism, including oil accumulation, in several plant species. In this study, progressive changes in gene expression in embryos and seed coats at different stages of seed development were comprehensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…In a previous study, genes related to fatty acid biosynthesis were grouped into two categories and detected in the early or later stages of seed development in tree peony [49]. Similarly, the coordinated regulation of multiple genes has been shown to promote the high accumulation of longchain unsaturated fatty acids in the seeds of tea oil camellia [50], and consistent results have been obtained in Brassica napus [51,52], Glycine max [53], and Linum usitatissimum [54]. Above all, the present results indicated that 40 days after fertilization could be a key point at which the first few steps of fatty acid biosynthesis are promoted in Z. armatum, and the subsequent reactions could be catalysed and completed in the stage occurring 62 days after fertilization, especially for long-chain fatty acid biosynthesis.…”
Section: Discussionmentioning
confidence: 57%
“…In a previous study, genes related to fatty acid biosynthesis were grouped into two categories and detected in the early or later stages of seed development in tree peony [49]. Similarly, the coordinated regulation of multiple genes has been shown to promote the high accumulation of longchain unsaturated fatty acids in the seeds of tea oil camellia [50], and consistent results have been obtained in Brassica napus [51,52], Glycine max [53], and Linum usitatissimum [54]. Above all, the present results indicated that 40 days after fertilization could be a key point at which the first few steps of fatty acid biosynthesis are promoted in Z. armatum, and the subsequent reactions could be catalysed and completed in the stage occurring 62 days after fertilization, especially for long-chain fatty acid biosynthesis.…”
Section: Discussionmentioning
confidence: 57%
“…Thus far, the functions of plant ACBPs have been widely elucidated in the eudicots, such as Arabidopsis and Brassica napus , although there have been many reports on the characterization of ACBP family members from other plant species, such as Oryza sativa , Agave americana , Vernicia fordii , Vitis vinifera , Helianthus annuus , Gossypium hirsutum , Jatropha curcas , and Elaeis guineensis (Du et al 2016 ; Raboanatahiry et al 2018 ; Liao et al 2019 ; Amiruddin et al 2020 ). Other than Arabidopsis and Brassica napus , the functions of ACBPs from other plant species have been mostly investigated using transgenic Arabidopsis (Takato et al 2013 ; Meng et al 2014 ; Panthapulakkal Narayanan et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Removing these contaminants is a critical step, as RNA with high purity and integrity is critical for gene expression analyses. Although there are several methods available for seed RNA extraction (Kanai et al, 2017;Pereira et al, 2017;Mornkham et al, 2013;Suzuki et al, 2004); fewer protocols are available for the extraction of good quality RNA from specific seed tissue types, especially for the seed coat (Jiang et al, 2019;Liao et al, 2019;Hong et al, 2017;Kour et al, 2014).…”
Section: Introductionmentioning
confidence: 99%